LEGAL CONSEQUENCES OF MEASUREMENT ERRORS IN LAND SALE AND PURCHASE AGREEMENTS: REVIEW OF THE OBLIGATIONS AND RIGHTS OF THE RELATED PARTIES BASED ON THE CIVIL CODE - Bred Klenten; Gunawan Djajaputra (RADJA PUBLIKA, 2025)
Land sales and purchase agreements are one of the most common transactions in daily life. An important element in this agreement is the measurement of the land being sold. However, measurement errors in land sale transactions often occur, which can lead to significant legal consequences for the parties involved. Measurement errors can affect the validity of the agreement and the rights and obligations of the parties, such as the seller and the buyer. According to the Civil Code (KUHPerdata), measurement errors in land can lead to the cancellation of the agreement, price reduction, and the obligation to compensate for the loss resulting from the difference in land area. Furthermore, both parties may negotiate or conduct a remeasurement to reach a fair resolution. If an agreement cannot be reached, the agreed party may file a lawsuit in court. Therefore, it is crucial to understand the legal implications of measurement errors in land sale agreements and the legal resolution procedures outlined in the Civil Code.